Kalam Insyā’ Ṭalabī Dalam Surah al-‘Alaq: Kajian Balaghah Terhadap Tuntutan Implisit - Idris Siregar; Intan Permata Maha; Ratu Diva Tanzilla Nasution; Muhammad Rezan Hasibuan (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2025)
This article examines the kalam insya' in Surah Al-'Alaq by emphasizing the function of the implicit demands contained in the command (amr) and rhetorical istifham. So far, studies of Surah Al-'Alaq have generally focused only on verses 1-5 as the first revelation revealed to the Prophet Muhammad, while the subsequent verses have not been widely analyzed in terms of balaghah, especially within the framework of kalam insya' thalabi. This study uses a qualitative-descriptive method with a balaghah analysis approach through the perspective of ma'ani science, by examining the linguistic structure of the verses of Surah Al-'Alaq and the rhetorical meanings they contain. The results of the study show that Surah Al-'Alaq does not only contain explicit demands such as the command iqra', but also implicit demands conveyed through rhetorical istifham, especially in verses 9-19. This form of istifham is not included to obtain a literal answer, but rather functions as an invitation to reflection, a moral critique of arrogance and rejection of guidance, and an affirmation of theological awareness of God's supervision. This study concludes that the kalam insya' thalabi in Surah Al-'Alaq serves as an effective Quranic rhetorical instrument in establishing continuity between the initial message of revelation and moral demands, while simultaneously strengthening the persuasive and dialogical character of the Quran.